El Ministerio de Instrucción Pública acaba de crear en Madrid el Instituto para Obreros - Amster, Mauricio
Arm raised holding textbooks with scenes of factories in background Suggested translation: The Ministry of Public Education has just created in Madrid the Institute for Workers PO-0072